Implementing a coaching culture in practice. Issue 7 (10th September 2021) - Davis, Rachel
Abstract : There is rising concern regarding wellbeing in the veterinary sector and this is not surprising considering the demands that the veterinary profession can sometimes put on individuals (Bartram and Baldwin 2010). In such high‐performance, high‐stakes environments, it can be difficult to make time for self development (Meehan 2019); however, it is in these sorts of environments that we need self‐management skills the most. How can we encourage vets to prioritise self care? Can we create working environments that are both operationally and financially productive, and that promote, rather than obstruct, professional wellbeing? This article discusses the benefits of adopting a coaching approach in your practice to support and drive both performance and wellbeing.